Improving Mathematical Understanding on Geometry for 9th Grade Students through Three-Dimensional Mathematics Learning Media Based on Virtual Reality - Simbolon, Kerdid; Ditasona, Candra; Setiawan, Laurencia Firstania (S&Co Publishing, 2024)
This study aimed to develop a three-dimensional virtual reality (VR)-based learning media for teaching mathematics at 9th grade students, focusing on improving students' understanding of geometric shapes. Utilizing the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model, the research involved the development of an interactive VR tool that allows students to engage with complex geometric concepts in an immersive environment. The VR media was validated by subject learning material experts in terms of content, language, and technical aspects, resulting in an overall validity score of 4.04, indicating high validity. Implementation quantitative analysis showed that the tool significantly improved student comprehension, with an average practicality score of 3.81, indicating that the media was easy to use in the classroom. This study concludes that VR-based learning media offers a promising approach to overcoming the difficulties students face in understanding three-dimensional geometry, providing both an engaging and effective learning experience.